2011
DOI: 10.1210/me.2010-0395
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Protein Restriction Elevates Cholesterol in Adult Rat Offspring Due to Repressive Changes in Histone Modifications at the Cholesterol 7α-Hydroxylase Promoter

Abstract: Adverse events in utero, such as intrauterine growth restriction (IUGR), can permanently alter epigenetic mechanisms leading to the metabolic syndrome, which encompasses a variety of symptoms including augmented cholesterol. The major site for cholesterol homeostasis occurs via the actions of hepatic cholesterol 7α-hydroxylase (Cyp7a1), which catabolizes cholesterol to bile acids. To determine whether posttranslational histone modifications influence the long-term expression of Cyp7a1 in IUGR, we used a protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
163
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(181 citation statements)
references
References 65 publications
13
163
2
3
Order By: Relevance
“…All diets and water were administered ad libitum. Previous studies by our laboratory have demonstrated that the food intake between both offspring groups is practically identical (Sohi et al 2011).…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…All diets and water were administered ad libitum. Previous studies by our laboratory have demonstrated that the food intake between both offspring groups is practically identical (Sohi et al 2011).…”
Section: Introductionmentioning
confidence: 73%
“…The decrease in Cyp7a1 leads to hypercholesterolemia in male offspring by 4 months (Sohi et al 2011). This was found to be due, in part, to repressive changes in histone modifications at the LXRE site of the Cyp7a1 promoter.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…IUGR could affect lipid metabolism possibly through altered liver growth or liver development or altered endogenous cholesterol synthesis or absorption. In addition, epigenetic mechanisms may be a part of the programming, given that, e.g., a recent report revealed histone modifications surrounding the Cyp7a1 promoter in hypercholesterolemic IUGR pups of protein-restricted dams (15). We did not determine how the food restriction during pregnancy affected the milk quality of the lactating dams.…”
Section: Discussionmentioning
confidence: 91%
“…Thus, in liver, maternal low protein intake alters gene expression of Igf2 and H19 by regulating DNA methylation (Gong et al, 2010) and induces changes in histone acetylation and methylation that affect genes regulating the amino acid response pathway (Zhou and Pan, 2011). Maternal low protein diet also elevates cholesterol in the offspring and induces changes in liver histone methylation status (Sohi et al, 2011). In skeletal muscle, it increases acetylated histone 3 and acetylated histone 4 at the C/EBPβ (Zheng et al, 2011b) and GLUT4 promoter regions (Zheng et al, 2011c) but only in female pups, indicating a sex-dependent adaptation.…”
Section: Calorie Restriction and Low Protein-dietsmentioning
confidence: 99%